Design of plasmonic nanoparticles and their use for biotoxin immunosensing - Zhang, Lu (Nanyang Technological University, 2019)
Gold nanoparticles (AuNPs) are widely used in the fields of biosensing, diagnostics, nanomedicine etc.1-5 Because of the incomparable affinity and specificity to target, antibody (Ab) as bioreceptor long has been used in conjunction with AuNPs. A good conjugation method should produce stable AuNP-Ab conjugates while maintaining the ability of the Ab to recognize and bind to its corresponding antigen. Thus, a robust conjugation method is of critical importance for improving the sensitivity of biosensors. To evaluate the coupling chemistry between Ab and AuNPs and quantify the Ab surface coverage on AuNPs, various quantification methods have been applied via direct or indirect approaches. In this review, we will focus on IgG-type antibodies conjugated to spherical AuNPs and present the strategies of conjugation, followed by quantification methods of Ab surface coverage, and finally selected applications in optical biosensing.